2022
DOI: 10.1371/journal.pone.0275713
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between women’s empowerment and household food and nutrition security in Pakistan

Abstract: Women’s empowerment is considered to play a crucial role in food and nutrition security. We aimed to explore the relationship between women’s empowerment and food and nutrition security, in rural Pakistan. Methods: To estimate women’s empowerment, we developed a Rural Women Composite Empowerment Index incorporating nine domains. For indicators of food and nutritional data we used data of 1879 rural households from Pakistan Rural Household Panel Survey (PRHPS). Food insecurity was measured through a caloric int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…Studies like Ishfaq et al (2022) have shown that health and cleanliness classes can help improve the health of women who live in rural areas. These programs focus on teaching about babies, stopping diseases and taking care of expectant mothers to improve the health levels of country women and their loved ones.…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies like Ishfaq et al (2022) have shown that health and cleanliness classes can help improve the health of women who live in rural areas. These programs focus on teaching about babies, stopping diseases and taking care of expectant mothers to improve the health levels of country women and their loved ones.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Women in Union Council Wahur face many problems that stop their social and financial growth. Existing research (Jaka & Shava, 2018;Ishfaq et al, 2022) shows large problems stopping rural women from getting education and jobs in the economy. This is made worse by social rules related to being female, along with the limited resources they have access to.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleh karena itu, perempuan dapat mengambil peran dalam menjaga ketahanan pangan di masyarakat, seperti peran kelompok tani perempuan dalam memperkuat ketahanan pangan. Perempuan pedesaan memainkan peran penting dalam pertanian, mewakili 43% tenaga kerja pertanian di dunia dan di negara berkembang serta memproduksi 50% pangan dunia (Akter et al, 2017;Ishfaq et al, 2022).…”
unclassified
“…Lokasi di Desa Calingcing, Kabupaten Tasikmalaya, memiliki beberapa petani perempuan yang mengolah lahan pertanian untuk memperkuat ketahanan pangan dari aspek kuantitas dan kualitas. Perempuan berperan penting dalam menjaga ketahanan pangan dan gizi (Ishfaq et al, 2022). Banyak organisasi internasional telah mengungkapkan bahwa pemberdayaan perempuan merupakan bagian dari prioritas kebijakan mereka (Perserikatan Bangsa-Bangsa, 2023).…”
unclassified